Evolution characteristics and pattern optimization of land use conflict in inland river Basin from the perspective of production-living-ecological - Wanzhuang Huang; Ziyang Wang; Yue Liu; Jing Shi (PLoS ONE, 2025)
Identification of the process and intrinsic mechanisms of land use conflicts is a prerequisite for adjusting optimal national spatial planning strategies. This paper, starting from the perspective of production-living-ecological, constructed a train of thought for optimizing national spatial planning in inland river basins, taking the example of the Shiyang River Basin. Based on the conflict measurement model of “source of risk - receptor of risk - effect of risk”, this paper analyzed the evolution of production-living-ecological land conflicts, employed a geographical weighted regression model to examine the influencing factors of the evolution of land use conflicts, and optimized the national spatial pattern as well as proposed regulation strategies. The results indicated that from 1990 to 2020, the area of unused land in the Shiyang River Basin decreased the most, mainly converted into farmland, construction land, and water areas. The transfer of land use mainly manifested as mutual transformation between production land and ecological land, followed by mutual transformation between production land and living land. During the research period, the overall complexity of land use presented a pattern of “high in the south and low in the north”, the overall vulnerability showed a pattern of “high in the central area and low in the surrounding areas”, and the overall stability was relatively high. The intensity of production-living-ecological land conflicts in the Shiyang River Basin showed an increasing trend, with the average conflict intensity rising from 0.44 to 0.57, exhibiting a spatial distribution pattern of “high in the central area and low in the surrounding areas”. The impact of road network density and river network density on the evolution of production-living-ecological land conflicts in the Shiyang River Basin was the most significant. The optimization results of national spatial patterns and regulation strategies could provide a scientific basis for the optimization and comprehensive management of national spatial planning in arid inland river basins.